Two new species of mole crickets (Orthoptera: Gryllotalpidae: Scapteriscinae) from the Colombian Amazon and Orinoquia rainforests - Cadena-Castañeda, Oscar J. (Zootaxa, 2011)
This paper describes and illustrates two new species of mole crickets of the genus Scapteriscus from the forest of the Colombian Amazon and Orinoquia regions, based on linear morphometry, level of coverage of tympanum, ocelli form, intraocellar distances, intraocular distances and interdactylar distances as proposed in Nickle in 2003. The interspecific relations of the new species are discussed.